Rab GTPases take centre stage in understanding Entamoeba histolytica biology. (2nd September 2020) - Verma, Kuldeep; Srivastava, Vijay Kumar; Datta, Sunando
ABSTRACT: Rab GTPases constitute the largest subgroup in the Ras superfamily of GTPases. It is well established that different Rab GTPases are localized in discrete subcellular localization and regulate the membrane trafficking in nearly all eukaryotic cells. Rab GTPase diversity is often regarded as an expression of vesicular trafficking complexity. The pathogenic amoeba Entamoeba histolytica harbours 91 Rab GTPases which is the highest among the currently available genome sequences from the eukaryotic kingdom. Here, we review the current status of amoebic Rab GTPases diversity, unique biochemical and structural features and summarise their predicted regulators. We discuss how amoebic Rab GTPases are involved in cellular processes such as endocytosis, phagocytosis, and invasion of host cellular components, which are essential for parasite survival and virulence.